Pengaruh sosial ekonomi petani terhadap tingkat pendapatan usaha tani karet di Desa Maro Sebo Kecamatan Jaluko Kabupaten Muaro Jambi - Fitria Wahyuni , Putri; Ridwansyah, M.; Nurhayani, Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2024)
This research aims to determine and analyze the socio-economic characteristics of rubber farming, as well as assessing the influence of factors such as price, number of dependents, land area, farmer's age, number of working hours, and level of education on rubber farming income in Maro Sebo Village. , Jaluko District, Muaro Jambi Regency. The variables used are price, number of dependents, land area, age of farmer, number of hours worked, and level of education. Data was obtained through a primary survey by distributing questionnaires to 119 respondents. The analysis was carried out using the multiple linear regression method using EViews 10 software. The results show that individually, variables such as price, number of dependents, land area and farmer's age contribute significantly positively to income from rubber farming. However, the impact of the number of hours worked, although positive, does not have statistical significance. On the other hand, education level shows an insignificant negative effect on income from rubber farming in Maro Sebo Village.